Kuwait : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper on Kuwait focuses on fiscal expenditures with the aim of identifying potential areas for reform. While the authorities' planned non-oil revenue measures are welcome, these alone will not reduce the authorities' fiscal deficit sufficiently, highlighting the importance of expenditure reforms. This paper draws from previous episodes of adjustment in Kuwait and conducts some benchmarking-comparing Kuwait's level of fiscal spending in various areas to that of peers-to identify areas for streamlining and efficiency improvement. Kuwait needs to implement fiscal consolidation to adjust to durably lower oil prices. The collapse in oil prices has resulted in substantial deterioration of both external and fiscal positions, leading to large fiscal financing needs. In order to preserve the fiscal buffers and provide equitable consumption of future generations, Kuwait needs to consolidate its fiscal position. While the planned tax reforms and repricing of government services are steps in the right direction, fiscal consolidation also needs to rely heavily on streamlining expenditures.